A Case of Small-Cell Neuroendocrine Carcinoma of the Gallbladder in a Background of High-Grade Biliary Intraepithelial Neoplasia. (28th October 2020) - Alkamachi, B; Sharaf Aldeen, B; Alhamar, M; Jaratli, H
Abstract: Introduction/Objective: Neuroendocrine carcinoma (NEC) of the gallbladder is a very rare neoplasia comprising 4% of all malignant gallbladder neoplasms. Most of NECs show molecular accumulation of TP53, while KRAS mutations are rare. Approximately 40% of Biliary intraepithelial neoplasia (BilIN) cases are associated by KRAS mutations as an early molecular event, whereas TP53 mutation appears to be a late molecular event. Methods: We report a case of a 62-year-old male who presented to emergency department for evaluation of abdominal pain associated with vomiting. Imaging studies demonstrated a distended gallbladder with small amount of pericholecystic fluid along with 5 mm calculus at the gallbladder neck consistent with symptomatic cholelithiasis and acute cholecystitis. No mass lesion was radiologically identified. A laparoscopic cholecystectomy was performed. Grossly, there was a thickened area of mucosa at the distal body-fundus, measuring 5.0 x 4.5 cm. Multiple calculi were present. On histology, thickened area showed sheets and nests of moulded small cells with hyperchromatic nuclei, brisk mitotic activity and confluent necrosis. A diagnosis of small-cell NEC is established, and confirmed by positive immunoreactivity to neuroendocrine markers (CD56, Synaptophysin) and epithelial markers (CK7 and CAM5.2). Multiple foci of high-grade BilIN were noted. Subsequent entire submission of the gallbladder revealed no adenocarcinoma present. The pathologic stage was pT2a pNX. Conclusion: In conclusion, this rare gallbladder carcinoma is found incidentally in a patient with acute cholecystitis symptoms and no clinical proof of mass lesion. In addition, there is a background of high-grade BilIN, which shares the molecular pathway of small-cell NEC. Therefore, awareness of such coexistence of these two pathologic entities in the same gallbladder, is essential to alert pathologists to look for the poorly-prognosis small cell NEC, whenever BilIN is encountered in random section of a gallbladder.